Pembuatan Video Profil Objek Wisata Rawatirta untuk Meningkatkan Kunjungan Wisatawan di Desa Sumberkedawung Leces Probolinggo - Mutinda Teguh Widayanto; Mohammad Saiful Bahri; Yekti Rahajeng (Institut Riset dan Publikasi Indonesia, 2021)
Optimizing the potential of resources for the benefit of the community deserves the support of all parties. The Rawatirta area has the potential to be developed as a tourist attraction which is expected to contribute to the government and the surrounding community. These efforts have not yielded the expected results because of the low number of tourist visits to tourist attractions. From the analysis carried out, it was found that the cause was the lack of promotion about the existence of the tourist attraction. The Academic Community of Economics Faculty of Panca Marga University tries to provide solutions to these problems through community service activities, namely making a wizard profile video and uploading it on the Youtube Channel. It is hoped that the promotion through the Youtube Channel can encourage people to be interested in doing tourism activities in Rawatirta